Dampak Tingkat Pengangguran, Kualitas SDM Variabel Mediasi Pada Pertumbuhan Ekonomi Kabupaten Karawang - Zahra, Alfia; R, Ridwan; Syaefulumam, Fahmi; Latif, Abdul; Apriani, Erna (Madani: Jurnal Ilmiah Multidisiplin, 2024)
One measure in assessing community welfare is the level of economic growth. Karawang district is one of the largest industrial cities in Indonesia with the highest minimum wage. This research aims to analyze the influence of the unemployment rate and the quality of human resources as mediating variables on the economic growth of Karawang district during the ten year period, namely 2013 to 2022. The method used in this research uses a quantitative analysis approach with secondary data sources. The data analysis method in the research is path analysis. The results of this research showed that the unemployment rate variable directly had no effect on the quality of human resources, the variable of HR quality directly had no effect on economic growth, the unemployment rate variable indirectly through the quality of HR had no effect on economic growth. The results of the research can be used as a reference for practicing researchers, academics and information users in further research related to regional economic growth and the factors that influence it.